Convergent validity and inter-rater reliability of a lower-limb multimodal physical function assessment in community-dwelling older adults - O’Brien, Myles W.; Neyedli, Heather F.; Bosquet, Laurent; Leadbetter, Brianna; Smith, Alex; Gallant, Francois; Tanguay, Pamela; Bélanger, Mathieu; Mekari, Said (Frontiers in Aging, 2023)
Introduction: Lower-limb physical function declines with age and contributes to a greater difficulty performing activities of daily living. Existing assessments of lower-limb function assess one dimension of movement in isolation or are not time-efficient, which discourages their use in community and clinical settings. We aimed to address these limitations by assessing the inter-rater reliability and convergent validity of a new multimodal functional locomotion assessment (FLA). Methods: The FLA consists of five major functional movement tasks. (rise from a chair, walking gait, stair ascending/descending, obstacle avoidance, and descending to a chair) performed consecutively. Forty-eight community-dwelling older adults (32 females; age: 71 ± 6 years) completed the FLA as well as a timed up-and-go, 30s sit-to-stand, and 6-minute walk test. Results: Slower FLA time was correlated with a slower timed up-and-go (=0.70), less sit-to-stand repetitions (=-0.65), and a shorter 6-minute walk test distance (=-0.69; all, p<0.001). Assessment by two raters were not different (12.28 ± 3.86s versus 12.29 ± 3.83s, p=0.98; inter-rater reliability =0.993, p<0.001), and statistically equivalent (via equivalence testing). Multiple regression and relative weights analysis demonstrated that FLA times were most predicted by timed up-and-go performance (Adjusted R2=0.75; p<0.001; raw weight 0.42 [95% CI: 0.27, 0.53]). Discussion: Our findings document the high inter-rater reliability and moderate-strong convergent validity of the FLA. These findings warrant further investigation into the predictive validity of the FLA for use as an assessment of lower-limb physical function among community-dwelling older adults.